Patient Preferences for Chronic Myeloid Leukemia Medication Regimen Attributes and their Potential Impact on Adherence: Results from a Multi-national Conjoint Study - Ishan Hirji; Jessica Grinspan; Emuella Flood; Diana Chirovsky; Jennifer Devlen; Samuel Wagner; Catherine Davis (Journal of Health Economics and Outcomes Research)
**Background:** Tyrosine kinase inhibitors (TKIs) have significantly improved survival for patients with chronic myeloid leukemia (CML) but require long-term administration and non-adherence due to regimen requirements has been reported.